Respuesta :

znk

Answer:

Pb(NO₃)₂ + K₂CrO₄ ⟶ PbCrO₄ + 2KNO₃

Step-by-step explanation:

The unbalanced equation is

Pb(NO₃)₂ + K₂CrO₄ ⟶ PbCrO₄ + KNO₃

Notice that the complex groups like NO₃ and CrO₄ stay the same on each side of the equation.

One way to simplify the balancing is to replace them with a single letter.

(a) For example, let X = NO₃ and Y =CrO₄. Then, the equation becomes

PbX₂ + K₂Y ⟶ PbY + KX

(b) You need 2X on the right, so put a 2 in front of KX.

PbX₂ + K₂Y ⟶ PbY + 2KX

(c) Everything is balanced. Now, replace X and Y with their original meanings.  The balanced equation is

Pb(NO₃)₂ + K₂CrO₄ ⟶ PbCrO₄ + 2KNO₃